Obesity and genetics - Quiroga de Michelena, María Isabel (2017)
Obesity is becoming epidemic in many countries, and includes urban areas of Peru. Various studies try to elucidate the factors that contribute to this dangerous epidemic that has an evident genetic component. In this review we try to summarize what is currently known with respect to genetics in obesity.